(untitled) (AmeriQuests, 2012)
This book review examines University of Washington professor Charles LaPorte’s most recent work, Victorian Poets and the Changing Bible. LaPorte attempts to revise the model conventionally attributed to Victorian poetry as merely a product of Victorian culture. The chaste conservatism and religious dogmatism of Victorian culture may have been a reactionary attempt to salvage faith in the wake of doubt among the scientific community and even various disciplines of the humanities (most notably, finding the creation myth incompatible with Darwin’s theory of evolution, and the biblical accounts generally spurious in terms of historicity). Through an examination of the life and works of the Brownings, Tennyson, Clough, and Eliot, LaPorte argues that Victorian poetry actually embraced this doubt as the prospect for an open canon to which inspired poets could contribute new scriptures.